Gender Construction in Experiment-Based Biology Lessons - Kokott, Kira; Lengersdorf, Diana; Schlüter, Kirsten (My University, 2018)
Experimental investigations are an integral part of biology education because they demonstrate essential methods of obtaining knowledge in the natural sciences and generate high levels of learning activity. However, gender differences can arise during experimentation just as in other teaching situations. This article shows examples of social gender construction that may occur in experimental work. To this end, experimental group work was recorded on video and was assessed by the method of film image sequence analysis. The video segments revealed clearly distinguishable behavioral patterns used by the students to establish an identification as a girl or boy. For example, gender-related differences referred to preferring household appliances (girls) or technical instruments (boys) when experimenting, and acting in an attentive (girls) or attention seeking way (boys) during group work. The disadvantage of these patterns is that they may restrict the unfettered development of the personality and, among other things, make it difficult for girls to feel competitive in experimental sciences. In order to balance the situation, teachers must be able to notice these patterns and must know about strategies to broaden students’ behavioral range. Concrete proposals for such strategies being applicable in biology lessons but also in other subjects are given in the discussion of this article.
Keywords: Geschlechterkonstruktion; Biologie; Unterricht; Schule; Sozialisation; 371 Schulen, schulische Tätigkeiten; Sonderpädagogik; Experiment